Promoting Glycemic Well-Being Through NEAT: A Salutogenesis-Based Analysis Using Ordinal Logistic Regression - Mayasari, Ayu Citra; Rinarto, Nisha Dharmayanti; Setyani, Renata Deby Nanda (Universitas Airlangga, 2026)
Background: Adolescent glycemic well-being is increasingly recognized as a fundamental component of lifelong metabolic health. Within the salutogenic framework, non-exercise activity thermogenesis (NEAT) serves as a modifiable health-promoting behavior that enhances physiological resilience and supports glucose regulation. However, empirical evidence regarding NEAT as a salutogenic resource among Indonesian adolescents remains limited. Objective: This study aimed to analyze NEAT‘s role in determining glycemic status among adolescents and to identify significant predictors using Ordinal Logistic Regression. Methods: An analytic cross-sectional study was conducted among 101 adolescents at SMAN 1 Menganti, Gresik, selected through simple random sampling. NEAT was indirectly estimated as total energy expenditure (TEE) minus basal metabolic rate (BMR) and the thermic effect of food (TEF). Glycemic status was classified according to American Diabetes Association (ADA) criteria as normal, prediabetes, or diabetes. Data were analyzed using ordinal logistic regression with a significance level of p < 0.05. Results: Most adolescents exhibited normal glycemic status (73.3%), followed by prediabetes (26,7.8%). A family history of diabetes emerged as the strongest predictor of poorer glycemic category (OR = 34.88, p < 0.001). NEAT demonstrated a significant protective effect (OR = 1.004, p = 0.010), indicating that higher NEAT levels were associated with a reduced likelihood of progression to worse glycemic categories. Conclusions: NEAT is a key health-promoting resource that supports metabolic resilience and glycemic well-being in adolescents. Simple, low-cost strategies to increase daily movement may effectively improve glycemic health, supporting the need for salutogenesis-oriented school interventions in adolescent health promotion.